2019
DOI: 10.1029/2019jg005210
|View full text |Cite
|
Sign up to set email alerts
|

Humid Subtropical Forests Constitute a Net Methane Source: A Catchment‐Scale Study

Abstract: Commonly, well‐drained forest soils are net methane (CH4) sinks, whereas poorly drained soils in groundwater discharge zones could contribute significant CH4 emissions. Climate change is projected to bring more summer precipitation extremes to subtropics, which may affect forest CH4 balance. Chinese forests often have a hilly topography with well‐drained hillslopes and pronounced groundwater discharge zones. Although different landscape elements are likely to have different source and sink functions for CH4, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
(194 reference statements)
1
9
0
Order By: Relevance
“…In Northwest China, after a moderate N addition of 20 kg N ha −1 yr −1 , Song et al [55] reported a clear switch of CH 4 sink to source in the temperate forest soils, although the sink strength was small (about 6 µg CH 4 m −2 h −1 ). In a N-saturated subtropical forest located in Southwest China, Yu et al [22] reported significant soil CH 4 emissions during monsoonal summers that was comparable with wetland soils. Therefore, the potential contribution of methanogens should not be overlooked in future research in upland soils from Chinese forests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Northwest China, after a moderate N addition of 20 kg N ha −1 yr −1 , Song et al [55] reported a clear switch of CH 4 sink to source in the temperate forest soils, although the sink strength was small (about 6 µg CH 4 m −2 h −1 ). In a N-saturated subtropical forest located in Southwest China, Yu et al [22] reported significant soil CH 4 emissions during monsoonal summers that was comparable with wetland soils. Therefore, the potential contribution of methanogens should not be overlooked in future research in upland soils from Chinese forests.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the mechanism that enhanced NH 4 + concentration intensifies the competition with CH 4 for CH 4 mono-oxygenase catalyzing CH 4 oxidation [32,33], and methanotroph bacteria prioritize NH 4 + oxidation, resulting in reduced soil CH 4 uptake. In a N-saturated forest in China, Yu et al [22] even reported positive CH 4 fluxes from upland soils. This confirms that CH 4 uptake by methanotrophs is strongly dampened due to excessive N presented in soils.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such discrepancy may be explained by more complete denitrification to N 2 in periodically submerged soils (Koehler et al, 2012) and illustrates the importance of topographic positions on N cycling and thus N 2 O emission (Wexler et al, 2014;Yu et al, 2016). Previous works have also revealed topographic control on CH 4 fluxes (Kaiser et al, 2018;Warner et al, 2018;Yu et al, 2019b). For example, Warner (2018) identified the transition zone between upland and valley bottom as a hotspot of CH 4 uptake in a temperate forests landscape.…”
Section: Introductionmentioning
confidence: 94%
“…One possible mechanism is that increased NH 4 + in soil competes with J o u r n a l P r e -p r o o f CH 4 for the reactive site of methane monooxygenase, the key enzyme for CH 4 oxidation (Bedard and Knowles, 1989). In water-saturated forest soils, net CH 4 emissions have been reported, pointing to a role of methanogenesis for net CH 4 flux in forest soils under a wet climate (Itoh et al, 2009;Kaiser et al, 2018;Yu et al, 2019b). Soil CH 4 production, i.e.…”
Section: Introductionmentioning
confidence: 99%